2020
DOI: 10.1088/1742-6596/1532/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blending Methods on the Properties of PLA/Gr Nanocomposites

Abstract: Polymer nanocomposites based on polylactic acid (PLA) and graphene (Gr) were blended via melt blending and solution mixing. The properties of hardness and melt flow index (MFI) were investigated with variables of Gr loading from 0.5–2.0 wt.% and the effect of poly(ethylene glycol) (PEG) as plasticizer. The PLA/Gr nanocomposites exhibited higher hardness compared with neat PLA for both methods of nanocomposites preparation which were due to stiffness effect from nanofiller. The loading of PEG in the PLA nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Obviously, as the PLA content in the CPCMs decreased, both the modulus and hardness showed a decreasing trend, while the depth showed an increasing trend. It has been reported that the modulus and hardness of pure PLA are 4.720 GPa and 0.2290 GPa, respectively, which are higher than those of the CPCMs [31], indicating that the load of PEG in the PLA composite material led to a slight decrease in hardness [32]. This is because the addition of PEG destroyed the crystallization of PLA, as analyzed by XRD and SEM.…”
Section: Analysis With Nanoindentationmentioning
confidence: 99%
“…Obviously, as the PLA content in the CPCMs decreased, both the modulus and hardness showed a decreasing trend, while the depth showed an increasing trend. It has been reported that the modulus and hardness of pure PLA are 4.720 GPa and 0.2290 GPa, respectively, which are higher than those of the CPCMs [31], indicating that the load of PEG in the PLA composite material led to a slight decrease in hardness [32]. This is because the addition of PEG destroyed the crystallization of PLA, as analyzed by XRD and SEM.…”
Section: Analysis With Nanoindentationmentioning
confidence: 99%
“…Blending two different polymers is diverse, and many approaches have been demonstrated and used, such as mechanical, melt blending, and solution blending. 57–59 The choice of the polymer material and the miscibility of polymer blends directly affect the morphology and surface properties of the micro-patterned membrane. Hence, the effect of blending a thermoplastic fluoropolymer on the self-assembly of PLA, and the incorporation of nanomaterials, specifically the ZnO NPs on the polymer structure and the chemical properties are investigated.…”
Section: Introductionmentioning
confidence: 99%